INTRODUCING WESTERN HUMAN RESOURCE MANAGEMENT PRACTICES TO CHINA: SHOPFLOOR WORKERS’ PERSPECTIVES - Jos Gamble (Asian Academy of Management Journal, 2006)
The management of host country employees is often portrayed as a particularly fraught dimension for multinational firms. The problems involved are considered exponentially greater when there are substantial institutional differences and 'cultural distance' between the host country and a firm's parent country, as is assumed to be the case for Western firms operating in China. Based upon detailed case study research conducted at a UK-invested firm in China between 1999 and 2003 and a comparative study of a Chinese state-owned firm, this paper explores the veracity of such assumptions. The findings indicate that Western human resource management practices can be transplanted successfully and questions the degree to which foreign-invested enterprises need to adopt 'the Chinese way of doing things'. Indeed, such practices can be innovative in the Chinese context and provide a competitive source of differentiation for multinationals as employees.